2012
DOI: 10.4161/cc.21645
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the response to targeted MEK inhibition in melanoma

Abstract: T he limitations of revolutionary new mutation-specific inhibitors of BRAFV600E include the universal recurrence seen in melanoma patients treated with this novel class of drugs. Recently, our lab showed that simultaneous activation of the Wnt/β-catenin signaling pathway and targeted inhibition of BRAF V600E by PLX4720 synergistically induces apoptosis across a spectrum of BRAF V600E melanoma cell lines. As a follow-up to that study, treatment of BRAF-mutant and NRAS-mutant melanoma lines with WNT3A and the ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
(57 reference statements)
3
27
0
Order By: Relevance
“…Negative regulation of WNT/β-catenin signaling by MAPK pathway was confirmed in an additional study [141]. Treatment of BRAF-mutant and NRAS-mutant melanoma lines with WNT3A and the MEK inhibitor AZD6244 induces apoptosis.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Negative regulation of WNT/β-catenin signaling by MAPK pathway was confirmed in an additional study [141]. Treatment of BRAF-mutant and NRAS-mutant melanoma lines with WNT3A and the MEK inhibitor AZD6244 induces apoptosis.…”
Section: Introductionmentioning
confidence: 76%
“…Treatment of BRAF-mutant and NRAS-mutant melanoma lines with WNT3A and the MEK inhibitor AZD6244 induces apoptosis. The susceptibility of BRAF- and NRAS-mutant lines to apoptosis correlated with negative regulation of Wnt/β-catenin signaling by ERK/MAPK signaling and dynamic decreases in abundance of the downstream scaffolding protein, AXIN1 [141]. WNT inhibitors such as PRI-724 (inhibitor of interaction between β-catenin and CBP) and OMP-54F28 (a fusion protein antagonistic to Fzd8) are starting to enter clinical testing in tumors other than melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib and tivantinib, a MET tyrosine kinase receptor inhibitor, were used in 8 patients with NRAS -mutant melanoma, with 2 patients achieving a complete or partial response and 2 additional patients experiencing best responses of stable disease (61). Preclinical data also suggest that combining inhibitors of MEK and WNT signaling, as well as AKT/nuclear factor κB inhibition, may have value in NRAS -mutant melanoma (62, 63). Targeting the molecular chaperone heat shock protein 90 (HSP90) is one strategy that allows the simultaneous suppression of multiple downstream targets of RAS signaling.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Gopal et al have reported that the PI3K/AKT pathway plays a critical role in the antitumor efficacy of selumetinib in BRAF mutant melanoma, and inhibition of PI3K/AKT pathway results in synergistic antitumor activity with selumetinib 22. Because it has been reported that activation of Wnt/β-catenin signaling pathway inhibits tumor growth in mouse models of melanoma,23 the combinatorial effect of Wnt/β-catenin activation and selumetinib was examined 24. The combination of selumetinib and WNT3A, a ligand of Wnt/β-catenin pathway, induced apoptosis of melanoma cell lines harboring BRAF or NRAS mutations by degradation of AXIN1, a negative regulator of Wnt/β-catenin signaling 24.…”
Section: Selumetinibmentioning
confidence: 99%